2020
DOI: 10.1099/ijsem.0.004380
|View full text |Cite
|
Sign up to set email alerts
|

Strains of Bradyrhizobium cosmicum sp. nov., isolated from contrasting habitats in Japan and Canada possess photosynthesis gene clusters with the hallmark of genomic islands

Abstract: The taxonomic status of two previously characterized Bradyrhizobium strains (58S1T and S23321) isolated from contrasting habitats in Canada and Japan was verified by genomic and phenotypic analyses. Phylogenetic analyses of five and 27 concatenated protein-encoding core gene sequences placed both strains in a highly supported lineage distinct from named species in the genus Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…jicamae and B. elkanii ), a result that is in accord with the topology of robust gene trees generated from recent phylogenomic studies of the genus Bradyrhizobium [4, 7, 21]. The tree in further shows that novel strains 323S2 and 144S4 T (sv.…”
Section: Phylogenetic Analyses Using Partial Gene Sequencessupporting
confidence: 81%
See 1 more Smart Citation
“…jicamae and B. elkanii ), a result that is in accord with the topology of robust gene trees generated from recent phylogenomic studies of the genus Bradyrhizobium [4, 7, 21]. The tree in further shows that novel strains 323S2 and 144S4 T (sv.…”
Section: Phylogenetic Analyses Using Partial Gene Sequencessupporting
confidence: 81%
“…The genus Bradyrhizobium is a diverse group of species that includes economically important bacteria capable of forming nitrogenfixing symbioses with agricultural legumes such as soybeans [e.g., [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The grouping of Bradyrhizobium reference strains into these four superclades is consistent with the results of other phylogenetic studies of the genus Bradyrhizobium [ e.g . 1, 17, 18]. further shows that the novel strains are placed in two highly supported lineages corresponding to the proposed species ( B. septentrionale sp.…”
Section: Phylogenetic Analyses Of Partial Gene Sequencesmentioning
confidence: 76%
“…amphicarpaeae 39S1MB T [27], and, B. cosmicum 58S1 T and S23321 [18] lacking both symbiosis islands and plasmids contained the fewest ISs (range 5–15) whereas between 41 and 134 ISs were detected in Bradyrhizobium sp. DOA9 [28], Bradyrhizobium sp.…”
Section: Genomics Analysesmentioning
confidence: 99%
“…The internal nodes of B. cosmicum S23321 and 58S1 were located on the same branch as B. lupini USDA-3051 and B. canariense SEMIA-928, which are symbionts of Lupinus agustifolius and Lupinus sp., and, thus, shared the most recent common ancestor. However, an assessment of branch lengths showed that the Lupinus symbiont was older than S23321 ( Wasai-Hara et al , 2020 ). The close phylogenetic background of the S23321 chromosome with other bradyrhizobia strains implies that this strain has the potential for mutualism after receiving the symbiosis toolkit from neighboring strains.…”
mentioning
confidence: 99%